An experimental task to measure proactive aggression under incentive condition: A Reward-Interference Task. (15th October 2019) - Zhu, Wenfeng; Wang, Huan; Xia, Ling-Xiang
Abstract: Proactive aggression refers to attaining personal goals or gains through aggressive means with prior deliberation and moral disengagement, and it can occur without provocation and with a low-level of anger arousal. The current study introduces a new task, a Reward-Interference Task (RIT), to induce and measure proactive aggression in the laboratory under incentive conditions and develops a task-related questionnaire (Interference/Non-interference Motivation Questionnaire, INIMQ) through four experiments. The findings reveal that instrumental motivation toward incentives and moral motivation (moral disengagement and moral inhibition) were the main motivations for participants to attack opponents during the RIT. The validity and reliability of the INIMQ were acceptable, and the RIT had good internal consistency, adequate convergence, and discriminant validity. The present results show that the RIT is a valid tool for inducing and measuring proactive aggressive behavior under incentive conditions.